1980
DOI: 10.1002/app.1980.070251219
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigation of polyurethanes: Infrared spectroscopic investigations of monomeric and polymeric N,N′-diaryl ureas

Abstract: The carbonyl stretching vibration of crystalline N,N′‐diaryl ureas at 1640 cm−1 undergoes a very considerable shift to 1700 cm−1 when these compounds are in solution. This finding is of particular significance in connection with the hard segments of polyurethane elastomers. The absence of a carbonyl band at 1640 cm−1 in polyurethane–polyurea systems does not indicate the absence of urea groups or the reaction of urea groups to biuret groups. Urea groups may instead be present in the dissolved, i.e., noncrystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 2 publications
3
7
0
Order By: Relevance
“…When an "isolated" urea molecule is bonded to a DMSO molecule ( Figure 10), absorption occurs at the frequency of the "top" CdO. This result agrees completely with the experimental results found in the literature 10,13,28 where disubstituted ureas in DMSO solution absorb at 1695 cm -1 . In a recent publication, 16 the band around 1665 cm -1 was assigned to CdO from urea groups hydrogen-bonded to a single NsH.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…When an "isolated" urea molecule is bonded to a DMSO molecule ( Figure 10), absorption occurs at the frequency of the "top" CdO. This result agrees completely with the experimental results found in the literature 10,13,28 where disubstituted ureas in DMSO solution absorb at 1695 cm -1 . In a recent publication, 16 the band around 1665 cm -1 was assigned to CdO from urea groups hydrogen-bonded to a single NsH.…”
Section: Resultssupporting
confidence: 89%
“…This is in a qualitative agreement with the experimental results found in the literature. 10,28,29 The CdO bond distance increases when hydrogen bonds are formed and the corresponding absorption decreases in frequency, as expected, but other very interesting results arise from a closer examination. In the graph number of urea molecules-wave number ( Figure 10) we can observe that the "isolated" molecule absorbs at the highest frequency.…”
Section: Resultssupporting
confidence: 66%
“…This secondary reaction leads to a decrease in PUs molecular weight. 30 The δN-H + νC-N intensity increases at 1511 cm À1 indicating the HS hydrolytic degradation. 28 Besides, in these spectra appears one new absorption band at 1800 cm À1 called amide I carbonyls stretching vibrations characteristic.…”
Section: Resultsmentioning
confidence: 97%
“…After being immersed in water, this is the reaction product between the isocyanate and the amine group. This secondary reaction leads to a decrease in PUs molecular weight 30 . The δN–H + νC‐N intensity increases at 1511 cm −1 indicating the HS hydrolytic degradation 28 .…”
Section: Resultsmentioning
confidence: 98%
“…This technique allows detecting the variation of functional groups at different periods, which is based on the change of the absorbance of the functional groups in FTIR spectra in the reaction process. For instance, Hocker 6 reported that the carbonyl group present in soluble urea (1715 cm À1 ) interacts sooner with urethane carbonyls (1730 cm À1 ) than that of soluble D-urea (1697 cm À1 ). Michael 7 has study the reaction kinetics and development of structure during foam formation in model flexible polyurethane foam systems with FTIR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%